PENINGKATAN KEMAMPUAN BERBICARA MENGGUNAKAN METODE BERMAIN DRAMA DI KELAS IV SDN 2 DUWET KECAMATAN PANARUKAN - Aenor Rofek; Mory Victor Febrianto (CERMIN: Jurnal Penelitian, 2018)
Speaking skills are skills for expressing ideas, thoughts, and feelings verbally. Speaking is a form of communication that shapes human behavior that utilizes physical factors, namely utterances, in the form of sounds, body movements, expressions to reinforce the content of speech. Based on preliminary observations done on April 23, 2018 at SDN 2 Duwet, as many as 33 students could not communicate well; they were shy in expressing opinions in discussion forums. They were also unable to asnwer questions given by the teacher. In this study, the researchers tried to overcome these problems by implementing drama method. In cycle one (1) there was an increase in students’ speaking skills by 30%,, while in the second cycle (2) there was a 40% increase. Thus, it can be concluded that the use of the drama method is able to improve speaking skills of the fourth grade students.